Zn/MCM-41/MnO2 leclanché button cell R2025 for low rate applications - Mohd Zawi, Nor Liza; Othman, Raihan; Ani, Mohd Hanafi (Trans Tech Publications, Switzerland, 2012)
The present work reports the performance characteristics of Zn/MnO2 Leclanché cell employing an inorganic MCM-41 membrane separator. MCM-41 material comprises of one dimensional, hexagonally ordered silicates mesostructure. The main advantage of MCM-41 membrane is its 3-in-1 functional features, viz. as ionic exchange channels, insulating layer between electrodes and electrolyte reservoir. Zn/MnO2 cell is constructed approximately to the size of R2025 coin cell. As the fabrication technique of MCM-41 membrane is merely by dip-coating process, it offers two advantages. First, the membrane could be prepared sufficiently thin and thus minimizing the internal losses of the cell. Second, it enables the construction of bipolar cell configuration with ease. Consequently, the results obtained demonstrate the volumetric energy density of Zn/MCM-41/MnO2 R2025 button cell has been extended by almost fivefold from 5.6 Wh/l to 26 Wh/l as bipolar cell configuration is utilized.